Metabolite Profiling of Bryophyte Endophytes: Novel Antioxidants from Indonesian Mosses - Ferdinand Susilo; Ilyas Fakhrizal (Science Journal Get Press, 2026)
Indonesian bryophytes harbor diverse endophytic microorganisms that are promising sources of novel bioactive compounds with potential pharmaceutical and antioxidant applications. This study investigated the secondary metabolite profiles of endophytic fungi isolated from Indonesian moss species using liquid chromatography–tandem mass spectrometry (LC–MS/MS) and nuclear magnetic resonance (NMR) spectroscopy. A total of 47 fungal isolates belonging to five genera were obtained from mosses collected in Java and Sumatra, Indonesia. Metabolomic profiling detected 312 molecular features, indicating high chemical diversity among the isolates. Antioxidant screening using DPPH and ABTS assays identified 23 compounds with significant free radical scavenging activity. Principal component analysis (PCA) revealed clustering patterns based on host species, with endophytes from Leucobryum aduncum forming a distinct metabolomic group enriched in chromene-glycoside derivatives. Molecular networking analysis through the Global Natural Products Social Molecular Networking (GNPS) platform revealed a putative novel polyketide cluster absent from existing databases. Bioassay-guided fractionation and structural elucidation led to the discovery of four new compounds, leucobryosides A–D. Among them, leucobryoside A showed the strongest antioxidant activity with an IC₅₀ value of 12.3 ± 1.8 μg/mL, comparable to ascorbic acid. These findings highlight Indonesian bryophyte endophytes as valuable sources of natural antioxidant compounds for future pharmaceutical and biotechnological applications.